Case Study: A Case of owner-inflicted Humeral Fracture in a Dog: Veterinary and Legal Perspectives in Nigeria - Abubakar, Nura; Mshelia, P.C; Bodinga, A.H; Shehu, Zaid; Dunfawa, A.M; Ahmad, U.S; Lawali, Y.B; Dahiru, Ashiru; Muhammad, M.S; E.I Oviawe (Faculty of Veterinary Medicine Universitas Brawijaya, 2025)
A five-year-old mixed-breed dog was presented at the Veterinary Teaching Hospital, Usmanu Danfodiyo University, Sokoto, Nigeria, with acute lameness and severe pain in the right forelimb. The injury, resulting in a fracture, was sustained after the dog was intentionally struck by its owner as punishment. Initially believed to be accidental, the trauma was later confirmed as a result of intentional harm. The fracture was successfully managed through appropriate surgical intervention, followed by pain management and rehabilitation, leading to the dog's full recovery. This case underscores the need for veterinary professionals to be vigilant in recognizing signs of animal abuse and emphasizes the importance of educating pet owners on proper and humane treatment.